Healthcare professional attitude and social support: How do they affect the self-esteem of physically disabled people? - Ismail, Farhana Fakhira; Mohamed Noor, Zaswiza; Muda, Siti Mariam; Ab Rahman, Norny Syafinaz (Wolters-Kluwer, 2020)
Context: The attitude of healthcare professionals and social supports give big influence toward self-esteem of physically disabled people. Aims: To explore how impairments could affect the self-esteem of physically disabled people and how healthcare professionals and social support boost their self-esteem. Materials and Methods: This study was conducted qualitatively whereby face-to- face interviews were conducted among 10 participants with physical disabilities. Participants were recruited from two rehabilitation centres in Kuantan, namely Community-based rehabilitation and rehabilitation, occupational therapy, and physiotherapy of public hospital in Kuantan. Interviews were conducted using the developed interview guide that explored on the disabled peoples’ self-esteem and motivation, feelings toward attitude of the healthcare professionals, and satisfaction toward the physical, services, and social support from the healthcare professionals. Thematic analysis was done to identify the themes emerged from the interview transcripts. Results: Five males and five females with age ranging from 31 to 58 years were interviewed. Five are still working or studying post impairments. Participants claimed being low self-esteem resulted from negative perception from the society, issue of rejection, being discriminated, and difficulty in getting support from the society. Most of the participants asserted that they gained their motivation and self-esteem due to the continuous support from various groups, such as their spouses, family members, colleagues, employers, and healthcare professionals. Conclusions: Despite heavy workload and stressful working environment, positive attitude showed by the healthcare professionals is highly praised. Hence, this will indirectly improve the self-esteem, motivation, and rehabilitation progress of physically disabled people.